PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN MANAJEMEN BERBASIS SEKOLAH TERHADAP MUTU PENDIDIKAN DI SMPIT WIDYA CENDEKIA KOTA SERANG - YUHANITA YUHANITA; ANIS ZOHRIAH; APUD APUD (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to determine and describe the influence of the principal's leadership style and school-based management on the quality of education at SMPIT Widya Cendekia and SMPIT Al-Ghifari Serang City. This study uses a quantitative research approach using multiple regression analysis methods. This research consists of 3 research variables, namely: Principal leadership style as (variable X1), school-based management as (variable X2) and quality of education as (variable Y). Data collection techniques used in the form of observation, questionnaires and documentation. The number of respondents in this study were 50 teachers at SMPIT Widya Cendekia and SMPIT Al-Ghifari Serang City. The results of data analysis show that: (1) it is known that tcount 8.967 is greater than ttable with a value of 1.66, with a significance level of 0.000 0.05, the conclusion is the hypothesis Ha is accepted and H0 is rejected, thus it can be concluded that there is an influence between the Head Leadership Style Schools on the Quality of Education with an influence of 81.2%, (2) it is known that tcount 7.106 is greater than ttable with a value of 1.66, with a significance level of 0.000 0.05, the conclusion of the hypothesis Ha is accepted and H0 is rejected, thus it can be concluded that there is an influence between School-Based Management on the Quality of Education with an influence of 81%, (3) it is known that Fcount 24,986 > Ftable 3,294, with a significance level of 5%. In conclusion, Ha is accepted and Ho is rejected, thus it can be concluded that the Principal's Leadership Style and School-Based Management affect the Quality of Education by 81%. In accordance with the table